Penetapan Kadar Total Fenol dan Total Flavonoid pada Lotion Berbahan Ekstrak Daun Sisrsak (Annona muricata) dan Kulit Buah Naga Merah (Hylocereus polyrhizus) Menggunakan Spektrofotometri UV–VIS - Suci Rahmadani Siregar; Suprianto; Chandra Pranata; Intan Coni Caroline Marbun (Jurnal Indah Sains dan Klinis, 2025)
Background: Phenolic and flavonoid compounds from soursop (Annona muricata) leaves and red dragon fruit (Hylocereus polyrhizus) peel have potential applications in lotion formulations; therefore, their quantification is important for quality evaluation. Objective: To determine total phenolic content (TPC) and total flavonoid content (TFC) in lotion formulations containing combined plant extracts and to assess the analytical method performance. Method; Four formulations were prepared: F0 (without extract), F1 (0.5% + 0.5%), F2 (1.0% + 1.0%), and F3 (1.5% + 1.5%). TPC was measured using the Folin–Ciocalteu method (mg GAE/g) and TFC using the AlCl₃ colorimetric method (mg QE/g). Method validation included repeatability (%RSD, n = 6) and spike-recovery accuracy at 80–120%. Results: The method showed good precision (%RSD 1.08% for TPC and 1.21% for TFC) and acceptable accuracy with recoveries of 98–102%. F0 showed non-detectable values, while increasing extract concentration resulted in higher TPC (3.82 ± 0.14 to 9.71 ± 0.33 mg GAE/g) and TFC (0.86 ± 0.05 to 2.35 ± 0.10 mg QE/g). Differences among formulations were statistically significant (p < 0.05). Conclusion: The UV–Vis method is suitable for determining TPC and TFC in lotion matrices, and higher levels of combined extracts significantly increase both parameters, supporting their use for quality standardization of herbal lotions.